Lemierre's Syndrome Caused by Klebsiella pneumoniae in a Diabetic Patient: A Case Report and Review of the Literature - Chuncharunee, Alan (Hawaii J Med Public Health, 2015)
Lemierre's syndrome is characterized by an oropharyngeal infection with internal jugular vein thrombosis followed by metastatic infections in other organs. This infection is usually caused by Fusobacterium spp. In this report, we present a rare case of Klebsiella pneumoniae-associated Lemierre's syndrome in a patient with poorly-controlled diabetes mellitus. The infection was complicated by septic emboli in many organs, which led to the patient's death, despite combined antibiotics, anticoagulant therapy, and surgical intervention. Therein, a literature review was performed for reported cases of Lemierre's syndrome caused by Klebsiella pneumoniae and the results are summarized here.